PERUMUSAN USULAN PROSEDUR PEMBARUAN INFORMASI GEOSPASIAL STUDI KASUS: KOTA BANDUNG - Dzun Nurwinas S., Muhammad
Geospatial information is information that includes location elements represented by basic forms such as points, lines, and areas. This information was created to match the actual conditions on the earth's surface. However, over time, changes occur on the earth's surface, necessitating updates to geospatial information. This study proposes a procedure for updating geospatial information, considering the absence of established standards related to the technical aspects of updating geospatial information. Starting with the availability of aerial photogrammetry data of Bandung City produced in 2016, this study will observe the changes that have occurred by re-acquiring aerial photo data using unmanned aerial vehicles in two areas of Bandung City in 2022. Based on the comparison results, changes were identified, such as the addition of new objects, the disappearance of old objects, and changes in the shape of objects. However, no horizontal position changes were observed for objects that did not undergo appearance changes, with the average differences in easting and northing values being -0.002 and -0.025 meters, respectively. This is peculiar because changes in position were observed at reference points, namely the CORS CLBG and CANG stations, with easting and northing changes of 0.15 and -0.04 meters. This could be due to the use of the real-time kinematic method in establishing ground control points, suggesting that in its data communication, this method has corrected the coordinate changes of the stations over time. Therefore, the methods used in this study, from data acquisition to processing, can serve as a basis for formulating an updating procedure.